MODAL PSYCHOLOGY WITH WORK ENGAGEMENT IN ONE OF THE LARGEST RETAIL COMPANIES IN INDONESIA - Nia Tri Setyawati; Sutarto Wijono (Journal of Social Research, 2022)
Background: The current pandemic has changed the order of life and has had a direct or indirect impact on workers. These changes occur in various aspects of life, including social aspects which then make workers have to experience changes in the work system such as working from home and working from office which are adapted to ongoing conditions in the workplace area. Objective: To find out the relationship between psychological capital and work engagement in one of the largest retail companies in Indonesia. Methods: This study uses a quantitative approach with a correlational design. This research was conducted to determine the relationship between psychological capital and work engagement in employees in retail companies. Results: After data analysis, it was known that the description of the subjects in this study was based on age, gender, level of education, length of work and employee status. From the results of the data obtained, it can be seen that there are more employees with an age range of 36-45 years with a percentage of 50% and more male employee subjects with a percentage of 91.7%. Conslusion: Based on research that has been conducted on 60 employees of retail companies, it is known that the hypothesis proposed in this study is accepted, namely that there is a significant positive relationship between psychological capital and work engagement which is indicated by the pearson correlation value (r-calculate) = 0.656 and greater than the r-table, which is 0.254 (r count > r-table).